Test on Discarding Tailings of Waste Rocks of a Vanadium-titanium Magnetite in Panxi Area - Jianping WANG; Weiwei LI; Deqiang LUO; Xuehong WU (Kuangchan zonghe liyong)
The combined methods of dry-discarding and wet-discarding were used to separate the vanadium-titanium-magnetite waste rock in Panxi. The results indicated that the grades of TFe and TiO2 which existed in the tailings reached 9.96% and 3.92%, respectively, and the recovery reached 23.73% using the dry-discarding method after the waste rocks were crushed to -40 mm. In addition, after the concentrates of dry-discarding were crushed to -5 mm, using the wet-discarding method, the grades of TFe and TiO2 which existed in the tailings reached 7.86% and 2.81%, respectively, and the recovery reached 27.36%. Finally, the discarding rate reached 51.09% using the combination methods of dry-discarding and wet-discarding, and the TFe grade of concentrate increased 5.56 percentage, TiO2 grade increased 2.75 percentage. The method could greatly reduce the subsequent grinding amount, improve the initial grade, and reduce the mineral processing cost.